2016
DOI: 10.1038/srep37982
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs are down-regulated in KRAS mutant colon cancer cells and can be transferred to exosomes

Abstract: Recent studies have shown that circular RNAs (circRNAs) are abundant, widely expressed in mammals, and can display cell-type specific expression. However, how production of circRNAs is regulated and their precise biological function remains largely unknown. To study how circRNAs might be regulated during colorectal cancer progression, we used three isogenic colon cancer cell lines that differ only in KRAS mutation status. Cellular RNAs from the parental DLD-1 cells that contain both wild-type and G13D mutant K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
245
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(251 citation statements)
references
References 57 publications
4
245
0
2
Order By: Relevance
“…However, the diversity of exRNA is extensive and microRNAs (miRNAs) are not the most abundant class of RNA found in EVs (Fritz et al, 2016; Mateescu et al, 2017). Analysis of cellular versus exRNA has repeatedly demonstrated selective biogenesis, export, and/or stability of specific RNAs (Cha et al, 2015; Dou et al, 2016; Kosaka et al, 2010; Santangelo et al, 2016; Skog et al, 2008; Squadrito et al, 2014; Valadi et al, 2007; Villarroya-Beltri et al, 2013; Wei et al, 2017). Elucidation of the mechanisms for selective sorting of cargo into EVs is critical to understanding extracellular signaling by RNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diversity of exRNA is extensive and microRNAs (miRNAs) are not the most abundant class of RNA found in EVs (Fritz et al, 2016; Mateescu et al, 2017). Analysis of cellular versus exRNA has repeatedly demonstrated selective biogenesis, export, and/or stability of specific RNAs (Cha et al, 2015; Dou et al, 2016; Kosaka et al, 2010; Santangelo et al, 2016; Skog et al, 2008; Squadrito et al, 2014; Valadi et al, 2007; Villarroya-Beltri et al, 2013; Wei et al, 2017). Elucidation of the mechanisms for selective sorting of cargo into EVs is critical to understanding extracellular signaling by RNA.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that specific intracellular oncogenic signaling events can regulate trafficking of miRNAs through phosphorylation of Argonaute (AGO) proteins (McKenzie et al, 2016). More recently, we identified a global downregulation of circular RNAs (circRNAs) in mutant KRAS cells with an inverse upregulation in EVs (Dou et al, 2016). Here, we report comprehensive analysis of EV long RNAs (>200 nt) and show that similar to miRNA export, there is selective export of long RNAs to EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, most of the investigated circRNAs were extracted from tissue samples; only one study combined tissue and plasma to assess the diagnostic value of circRNAs [32]. As previously reported, circRNAs are enriched and stable in exosomes [51, 52], which indicates that it might be possible to diagnose cancer by detecting plasma or serum circRNAs. It is believed that circRNAs could be useful as a noninvasive tumor screening tool for clinical practice in the future [53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aberrant expression of numerous circRNAs in disease, and the detection of these RNA species in the bloodstream have raised the exciting possibility that they may be used as noninvasive biomarkers. Indeed, the first studies revealed that circRNAs can be secreted in exosomes10 and that circulating circRNAs may be used as diagnostic biomarkers for type 2 diabetes mellitus,11 for risk stratification after myocardial infarction,12 and for cancer diagnosis 13…”
mentioning
confidence: 99%